Design And Implementation Of Store Atmosphere At Kharisma Swalayan - Faqih Mutaqin; Albari Albari (International Journal of Economics, Business and Innovation Research, 2024)
The establishment of the Kharisma Swalayan business is motivated by the opportunity to establish a branch of the old Kharisma store which still uses a shop system that is not modern to modern shops or what is commonly called supermarket by paying attention to various aspects of modern shops such as structuring store atmosphere in accordance with the times. Store atmosphere as a marketing communication tool that is designed in such a way as to meet the needs and desires of consumers and as an effort to understand consumer behaviour in modern retail stores in order to stimulate the desire to shop. Kharisma Swalayan is located in Petanahan, Kebumen. The development of kharisma Swalayan business includes operational, marketing, human resources, and financial plans. Some of the problems faced in the implementation of this business include how to keep optimising the store athmosphere to increase customer satisfaction and marketing strategies that are not easily copied by competitors. This implementation report covers the entire 6 months of business since the business idea was designed. Keywords: Business Design, Retail Business, Swalayan, Store Athmosphere, Marketing Strategy.